Pengembangan Media Pembelajaran Berbasis Android Materi Sistem Pencernaan Manusia untuk Meningkatkan Motivasi dan Hasil Belajar Peserta Didik Kelas V SD - Hartana, Albertus; Anjani, Brigita Vio Dwi (Belantika Pendidikan, 2022)
Abstract : This research has a purpose to develop of android-based learning media about the human digestive system to improve motivation and learning outcomes of fifth-grade elementary students; know the quality of android-based learning media about the human digestive system to improve motivation and learning outcomes of fifth-grade elementary students, and know the effectiveness of android-based learning media about the human digestive system to improve motivation and learning outcomes of fifth-grade elementary students. This research is a Research and Development (RD) type with the development model of ADDIE. The result of this research shows five steps in making the android-based learning media about the human digestive system 1) Analysis, 2) Design, 3) Development, 4) Implementation and 5) Evaluation. The quality of android-based learning media about a human digestive system based on the evaluation from 1) the expert of the subject gained an average score of 3,94 which is included in a Very Good category, 2) media expert gained an average score of 3,96 which is included in the Very Good category. Therefore, this android-based learning media about the human digestive system is proper to be used as the learning media. Based on the analysis of the improvement of study motivation using t-test, it was obtained sig (2-tailed)  0,0350,05. Based on the analysis of the improvement of the learning outcomes using t-test, it was obtained sig (2-tailed)  0,0220,05. In conclusion, the android-based learning media about the human digestive system is effective to improve the motivation and the learning outcomes of fifth-grade elementary students.Abstrak Abstrak: Penelitian ini bertujuan untuk: mengembangkan media pembelajaran berbasis android materi sistem pencernaan manusia untuk meningkatkan motivasi dan hasil belajar peserta didik kelas V SD; mengetahui kualitas media pembelajaran berbasis android materi sistem pencernaan manusia untuk meningkatkan motivasi dan hasil belajar peserta didik kelas V SD; dan mengetahui keefektifan media pembelajaran berbasis android materi sistem pencernaan manusia dalam meningkatkan motivasi dan hasil belajar peserta didik kelas V SD. Penelitian ini merupakan jenis penelitian pengembangan atau Research and Development (RD) dengan model pengembangan ADDIE. Hasil penelitian menunjukkan lima tahap dalam pembuatan Media Pembelajaran Berbasis Android: 1) Analysis, 2) Design 3) Development, 4) Implementation, dan 5) Evaluation. Tingkat kelayakan Media Pembelajaran Berbasis Android berdasarkan penilaian: 1) Ahli Materi diperoleh rerata skor 3,94 yang termasuk dalam kategori Sangat Baik, 2) Ahli Media diperoleh rerata skor 3,96 yang termasuk dalam kategori Sangat Baik. Dengan demikian, Media Pembelajaran Berbasis Android ini layak digunakan sebagai media pembelajaran. Berdasarkan analisis peningkatan motivasi belajar dengan uji-t diperoleh Sig. (2-tailed) 0,0350,05. Berdasarkan analisis peningkatan hasil belajar dengan uji-t diperoleh Sig. (2-tailed) 0,0220,05. Dengan demikian, Media Pembelajaran Berbasis Android Materi Sistem Pencernaan Manusia efektif untuk meningkatkan motivasi dan hasil belajar peserta didik kelas V SD.